Effect of dietary soybean saponin Bb on the growth performance, intestinal nutrient absorption, morphology, microbiota, and immune response in juvenile Chinese soft-shelled turtle (Pelodiscus sinensis) - Wang, Yue; Jia, Xinyue; Guo, Zixue; Li, Ling; Liu, Tianyu; Zhang, Peiyu; Liu, Haiyan (Frontiers in Immunology, 2022)
Numerous studies have manifested that dietary soybean saponin could decelerate the growth rate and induce intestinal inflammation in aquatic animals, but the possible causes were unclear. The juvenile Pelodiscus sinensis (mean initial body weight: 6.92 ± 0.03 g) were fed basal diet (CON group) and 2.46% soybean saponin Bb supplemented diet (SAP group) for 35-day to further explored the effects of dietary soybean saponin Bb on the growth performance, apparent digestibility coefficients, intestinal morphology, the gut microbiota, intestinal transporters/channels, and immune related genes expression. The results indicated that dietary soybean saponin Bb significantly decreased final body weight, specific growth rate, protein deposition ratio and apparent digestibility coefficients (dry matter, crude protein, and crude lipid) of nutrients in Pelodiscus sinensis, which maybe closely correlated with markedly atrophic villus height and increased lamina propria width in the small intestine. In addition, plasma contents of cholesterol, calcium, phosphorus, potassium, lysozyme and C3 were significantly decreased in SAP group compared with control group. Soybean saponin Bb significantly down-regulated the mRNA levels of glucose transporter 2, fatty acid binding protein 1 and fatty acid binding protein 2, amino acid transporter 2, b0,+-type amino acid transporter 1 and sodium-dependent phosphate transport protein 2b in small intestine. At the same time, the expressions of key transcription factors (STAT1, TBX21, FOS), chemokines (CCL3), cytokines (TNF, IL-8) and aquaporins (AQP3, AQP6) in inflammatory response were increased by soybean saponin Bb in large intestine of turtle. Additionally, dietary supplementation of SAP significantly reduced the generic abundance of beneficial bacteria (Lactobacillus, Bifidobacterium, and Bacillus) and harmful bacteria (Helicobacter and Bacteroides). In a nutshell, dietary supplementation of 2.46% soybean saponin not merely hindered the growth performance through negatively affecting the macronutrients absorption in the small intestine, but also induced inflammatory response in the large intestine possibly by damaging the intestinal morphology, disturbing the intestinal microbiota and decreasing intestinal epithelial cell membrane permeability.